FROM STRESS TO SUCCESS: HOW WORK-LIFE BALANCE AND ORGANIZATIONAL SUPPORT INFLUENCE EMPLOYEE PERFORMANCE - Moh Faizin; Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to investigate the impact of work-life balance, organizational support, and job stress on employee performance. The study sample consists of 134 individuals who are employed in the Grobogan Regency Regional Secretariat. This study employs a quantitative methodology. The conducted tests encompass validity and reliability assessments, f-tests and determination tests for model evaluation, multiple regression analysis tests, and hypothesis tests performed using SPSS 26. Studies indicate a strong and meaningful correlation between work-life balance, organizational support, work stress, and employee performance. Consequently, when the work-life balance, organizational support, and job stress levels rise, so does employee performance. Keywords: employee performance organizational support, work-life balance, work stress,